Impact of Atopic Dermatitis on Quality of Life, Tripoli Central Hospital - Hamida Al‑Dwibe; Mariam Briuin; Sabria El- Turki; Amina Drija (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Atopic dermatitis (AD) is a common, chronic, inflammatory skin disorder with an increasing prevalence. It has a significant effect on their quality of life, work productivity, activity impairment, and health care costs. This study was aimed to assess the impact of AD on quality of life of patients. Methods. Eighty-seven patients with atopic dermatitis attending dermatology eczema clinic in Tripoli Central Hospital were studied by using Dermatology Life Quality Index (DLQI) which is a self-administrated questionnaire to assess the type and degree of psychosocial impairment among atopic dermatitis patients. Data was analyzed using the SPSS software program version 16. Results. The age of patients was ranged from 3 to 78 years with mean age 18 ± 17 with males to female ratio 1.3:1. The impact of AD on quality of life of patients was significant among adults more than children. Conclusion. This study concludes that AD disease has a negative impact on the quality of life of adult patients, on social relationships, work, study, and on performing daily activities.